The variability of the serve toss in tennis under the influence of artificial crosswind - Mendes, Pedro C. (2013)
This study was made to analyze the variability and stability of the serve toss in tennis, on the x (side-to-side), y (back-to-front) and z (vertical) axes, with 12 experienced players under the influence of crosswind (induced aerodynamic flow) produced by an industrial ventilator. The players were analyzed individually after serving at maximum speed and accuracy to the intersection point of the centre line and service line ("T" point). The results allow us to conclude that the experienced players tend to stabilize the vertical dimension of the service (z axis). Additionally, this study confirms the invariability of the player height ratio: height of impact (1:1.5) in experienced players even when constrained by the "artificial crosswind." Given the above, the vertical dimension of the tennis serve is assumed as a constant feature, which is guaranteed in the remaining varying dimensions (y and x axes) of the ball toss. Thus, the variability should be seen as part of the solution and not as something to be avoided by players and coaches.